Disentangling Conscience Protections - Sawicki, Nadia N. (The Hastings Center report, 2018)
Earlier this year, the U.S. Department of Health and Human Services announced its intent to strengthen enforcement of legal protections for health care providers' conscience rights. It proposed regulations that would give the DHHS Office of Civil Rights greater authority to ensure that recipients of federal funding comply with federal conscience laws. This recent development creates an opportunity for scholars and policy-makers to revisit the perennial debate about whether and how law should protect health care providers' rights of conscience. Arguments about who should be protected, what actions should be protected, and whether there should be any limitations on the exercise of conscience rights have brought us no closer to a resolution. However, there is one remaining avenue for analysis that has, surprisingly, received very little attention—the question of how providers are protected, and from what consequences. Existing U.S. conscience laws immunize health care providers from a wide range of adverse consequences—including civil liability, criminal prosecution, administrative penalties, adverse action by employers, and discrimination by private actors, among others. However, academic and public policy debates rarely acknowledge the breadth of these protections. It is essential to disentangle this network of possible protections.